Czaszkogardlak – rzadki łagodny guz nowotworowy - opis przypadku = Craniopharyngioma – rare benign tumor – case report - Woźniak, Kamila; Ratuszek-Sadowska, Dorota; Śniegocki, Maciej (Journal of Education, Health and Sport, 2016)
Woźniak Kamila, Ratuszek-Sadowska Dorota, Śniegocki Maciej. Czaszkogardlak – rzadki łagodny guz nowotworowy - opis przypadku = Craniopharyngioma – rare benign tumor – case report. Journal of Education, Health and Sport. 2016;6(8):581-586. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60998 http://ojs.ukw.edu.pl/index.php/johs/article/view/3785 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 26.08.2016. Czaszkogardlak – rzadki łagodny guz nowotworowy - opis przypadku Craniopharyngioma – rare benign tumor – case report Kamila Woźniak1, Dorota Ratuszek-Sadowska2, Maciej Śniegocki1 1. Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2. Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Streszczenie Czaszkogardlak (guz Erdheima, łac. craniopharyngioma) to stosunkowo rzadki, łagodny guz nowotworowy o lokalizacji wewnątrzczaszkowej, wywodzący się z pozostałości kieszonki Rathkego. Nazwę craniopharyngioma wprowadził Harvey Cushing w 1932. Jedne z pierwszych prób operacyjnego leczenia guza podjął Ludvig Puusepp w 1923 roku. Objawy kliniczne zależą od lokalizacji guza. Są to przede wszystkim objawy wynikające z ucisku masy guza na sąsiadujące struktury anatomiczne. Autorzy przedstawiają opis przypadku klinicznego, leczonego operacyjnie w Klinice Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej Szpitala Uniwersyteckiego nr 1 im. dr A. Jurasza w Bydgoszczy z rozpoznanym w badaniu histopatologicznym craniopharyngioma. Słowa kluczowe: czaszkogardlak, craniopharyngioma, guz Erdheima, nowotwór łagodny. Abstract Craniopharyngioma (Erdheima tumor) is a relatively rare benign tumor of intracranial location, derived from the remnants of Rathke’s pouch. The name craniopharyngioma introduced Harvey Cushing in 1932. One of the first attempts at surgical treatment of the tumor took Ludvig Puusepp in 1923. Clinical symptoms depend on the site of a tumor. These are primarily the symptoms resulting from the comppression of the tumor mass on adjacent anatomical structures. The authors present a clinical case operating treated in the Department of Neurosurgery, Neurotraumatology and Pediatric Neurosurgery, Dr Antoni Jurasz University Hospital No.1 in Bydgoszcz histopathological diagnosed with craniopharyngoma. Key words: craniopharyngioma, Erdheima tumor, benign tumor.